The Anthropocene and the biodiversity crisis: an eco-evolutionary perspective - Jarne, Philippe (Comptes Rendus Biologies)
A major facet of the Anthropocene is global change, such as climate change, caused by human activities, which drastically affect biodiversity with all-scale declines and homogenization of biotas. This crisis does not only affect the ecological dynamics of biodiversity, but also its evolutionary dynamics, including genetic diversity, an aspect that is generally neglected. My tenet is therefore to consider biodiversity dynamics from an eco-evolutionary perspective, i.e. explicitly accounting for the possibility of rapid evolution and its feedback on ecological processes and the environment. I represent the impact of the various avatars of global change in a temporal perspective, from pre-industrial time to the near future, allowing to visualize their dynamics and to set desired values that should not be trespassed for a given time (e.g., +2 °C for 50 years from now). After presenting the impact of various stressors (e.g., climate change) on biodiversity, this representation is used to heuristically show the relevance of an eco-evolutionary perspective: (i) to analyze how biodiversity will respond to the stressors, for example by seeking out more suitable conditions or adapting to new conditions; (ii) to serve in predictive exercises to envision future dynamics (decades to centuries) under stressor impact; (iii) to propose nature-based solutions to the crisis. Significant obstacles stand in the way of the development of such an approach, in particular the general lack of interest in intraspecific diversity, and perhaps more generally a lack of understanding that, we, humans, are only a modest part of biodiversity.